Design and Prototyping of Mini AGV with Arduino Microcontroller - Sutisna, Nanang Ali; Farrand, Michael Quinn (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2020)
This paper presents the design and prototype of a Mini Automated Guided Vehicle (AGV) using a microcontroller. The mini AGV system is based on an autonomous forklift. The purpose of the AGV prototype is to move objects from one place to another and continuously. To run, AGV uses the Line Follower method by using four obstacle detection sensors or infrared transmitters and receivers. Furthermore, when all sensors are active, AGV will stop when there are objects with RFID tags outside. The RFID reader which is placed in front of the AGV activates a stepper motor which will move the object's fork. Then AGV sends the object to a predetermined place. Most components use compatible Arduino modules, except for the chassis and some parts use components made of acrylic or printed in 3D.